Analisis faktor-faktor yang mempengaruhi pengelolaan keuangan (Studi pada Generasi X) - Marshanda, Nabilla Diva; Wulandari, Dewi Ayu (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2024)
Purpose This research aims to analyze the influence of financial literacy, income, use of fintech, and materialism on the financial management of Generation X. Methodology of this research is quantitative research. The population in this study is Generation X who live in the Java Island region. The data used in this research is primary data by distributing questionnaires online using Google Forms. This research technique uses purposive sampling with the characteristics of Generation The sample in this study consisted of 115 respondents. Findings The results obtained are that financial literacy, income, and the use of fintech have a positive and significant effect on financial management, while income has a negative and significant effect on financial management. Suggestion for future researchers to add independent variables to strengthen the influence on the dependent variables and for Generation X they can improve aspects of variables whose values are still low.